The race of ecological vehicles: Consumer behavior and generation impact in the Portuguese market - Campino, J.; Mendes, F. P.; Rosa, Á. (SN Business & Economics, 2023)
The impacts of climate change are becoming increasingly severe and noticeable. Consumers are becoming more cognizant of the environmental challenges that affect the planet. A major contributor to carbon emissions and the resulting warming climate and pollution is transportation. As a result, the selection of environmentally friendly options in this industry is becoming a pressing matter. This study aims to examine the reasons that motivate consumers to choose eco-friendly vehicles. The study specifically aims to understand what factors drive consumers to purchase such vehicles. A questionnaire was administered to the Portuguese population to determine which factors influence the decision to purchase eco-friendly vehicles, and what type of vehicles are preferred. The study includes all types of eco-friendly vehicles, including early-stage solutions such as fuel cell vehicles. Furthermore, the study examines whether there is any difference in purchasing habits between generations. The study is based on several theories, including the Technology Acceptance Model (TAM), Diffusion of Innovation (DOI), Norm Activation Model (NAM), and Theory of Planned Behavior (TPB). Our research concludes that attitude (influenced by the advantages, compatibility, and non-complexity) and personal norms (influenced by the efficiency) are the two factors that affect positively and significantly the intention of purchase. The preferred eco-friendly vehicle among participants was found to be the hybrid electric vehicle, and the hydrogen fuel cell electric vehicle was also considered. The study did not find a significant impact of generation on purchasing decisions, but different generations were found to value different factors when making a vehicle purchase.